KKNM-Bimbingan Belajar Siswa SD Kelas 1 selama Masa Pandemi Covid 19 di Desa Kenere Kecamatan Solor Selatan Kabupaten Flores Timur - Tukan, Diana Awulina Bunga; Daud, Maimunah H (LPPM Universitas Flores, 2022)
Kenere Village is one of the villages in the South Solor sub-district, East Flores district. In this COVID-19 pandemic situation, community activities are limited so that teaching and learning activities for students in schools are also limited resulting in many students being careless in learning. Therefore, with the guidance carried out at school and following the provisions that students who come to school at least 4-5 people besides that guidance is also carried out from home or BDR with this guidance activity students are guided to train and guide students who are slow in learning to better study hard to get good results. Guidance activities are very influential on the learning process of elementary school children in grade 1, with this guidance many students experience changes before and after the activity. Students who are slow to learn can be overcome with tutoring and will foster good learning achievement. In this tutoring, the media or tools used are notebooks, pencils/pens, package books, letter cards and alphabetic calendars.